PARTISIPASI ANGGOTA KELOMPOK TANI DALAM PROGRAM KAWASAN RUMAH PANGAN LESTARI DI DESA MARGA KAYA KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Fitria Dwi Rahma Piska; Kordiana K Rangga; Dame Trully Gultom (Lampung University, 2020)
This study aims are to find out implementation of the Kawasan Rumah Pangan Lestari Program (KRPL), to know the level of community participation in the Program and the factors related to the participation. This study was conducted in November - December 2018 in the Marga Kaya Village Jati Agung Subdistrict South Lampung District. The method used was a survey method. The total of 46 respondents was used as samples by using proportional random sampling method. Correlation between variables were tested using Spearman Rank Correlation Test. KRPL is a home garden land use program by planting family medicinal plants and vegetables. The implementation of the KRPL program is the first year at the stage of growing members of farmer groups for funding of Rp. 15,000,000 in 2013. Some activities conducted in the program included nurseries, plot demonstrations, cultivating in yards, and assistance by extension agents. The second year, namely the development stage, the KRPL program that has been grown in the first year, will continue at the development stage. The third year is the stage of independence of the KRPL program that has developed the management of the KRPL. In this stage, the source of funds is obtained through self-help members of the group implementing the activities. The average participation rate of farmer group members in the program was 69.28 percent. Factors significantly related to the participation are knowledge about the program, education level, communication intensity, motivation level, and experience.Keywords: participation, kawasan rumah pangan lestari program, farmers